Always and forever, Lara Jean - Han, Jenny (2017)
As high school ends, Lara Jean looks forward to her father's remarriage and seeing her sister, but she must choose a college, prepare to leave home, and possibly leave her beloved Peter behind
Accelerated Reader AR
Keywords: Teenage girls -- Juvenile fiction; High school seniors -- Juvenile fiction; Decision making in adolescence -- Juvenile fiction; Dating (Social customs) -- Juvenile fiction; Korean American teenagers -- Juvenile fiction; Weddings -- Juvenile fiction; Teenage girls -- Fiction; High school seniors -- Fiction; Decision making in adolescence -- Fiction; Dating (Social customs) -- Fiction; Korean American teenagers -- Fiction; Weddings -- Fiction; Young adult fiction; Romance fiction